2015
DOI: 10.4028/www.scientific.net/amr.1089.159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 1-Methylcyclopropene Treatment on Peach Fruit (<i>Prunus persica</i> L.) for Extending Storage Life

Abstract: In order to maintain better quality of peach during cold storage and to extend the storage time, effects of different dose of 1-methylcyclopropene (1-MCP) treated of fresh kiwifruit on quality were investigated and the physiochemical attributes were subsequently evaluated during 60 days storage at 0 °C. Results showed that 1-MCP treatment had a high effect on inhibiting the respiratory rate, total soluble solid decrease and maintaining titratable acid content during the end of the storage compared with the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In peach, for example, involvement of endogenous ethylene production in the alleviation of postharvest fruit CI was reported in previous studies [1], and applying exogenous ethylene treatment markedly alleviated fruit CI [26,27]. However, the alleviation of CI by blocking ethylene action with 1-MCP was also found [29,30]. Such difference in ethylene effects on CI might be due to differences in species or variety, as well as ethylene treatment manners and application time in the different studies.…”
Section: Ethylene Is An Important Regulator Of Postharvest Chilling Imentioning
confidence: 86%
See 1 more Smart Citation
“…In peach, for example, involvement of endogenous ethylene production in the alleviation of postharvest fruit CI was reported in previous studies [1], and applying exogenous ethylene treatment markedly alleviated fruit CI [26,27]. However, the alleviation of CI by blocking ethylene action with 1-MCP was also found [29,30]. Such difference in ethylene effects on CI might be due to differences in species or variety, as well as ethylene treatment manners and application time in the different studies.…”
Section: Ethylene Is An Important Regulator Of Postharvest Chilling Imentioning
confidence: 86%
“…However, in peach fruit, the effect of ethylene on CI appears to be in dispute. Ethylene-alleviated and 1-MCP-induced CI has been reported in nectarines [25][26][27], which contrasted with some other reports where alleviation of CI was achieved by blocking ethylene action with 1-MCP [28,29]. On investigation of the mechanisms for alleviation of postharvest fruit CI in peach by low temperature conditioning (LTC), we previously found that the alleviation was related to a significantly enhanced ethylene biosynthesis during early stage of cold storage [1].…”
Section: Introductionmentioning
confidence: 85%